"Zealous imitation": the materiality of the crusader's marked body - Purkis, William J. (Material religion, 2018)
Drawing on textual evidence from across the Latin West and ranging from the eleventh to the fifteenth centuries, this paper explores the practice of crusader body-marking, whereby those who "took the cross" imposed cuts or brand-marks on themselves prior to their departure for the Holy Land. It is argued that these practices should be understood in part as an anxious response to the ephemeral nature of the crusader's cloth cross, the defining material object associated with the crusades, which was traditionally sewn on to clothing as an indication of the bearer's temporary commitment to imitate Christ through the medium of holy war. Further, by focusing in particular on the materiality of permanent body-marking practices, the paper argues that the experience of pain and suffering that was inevitably involved should be understood as an active expression of devotion towards Christ's body, and thus situated within a broader context of medieval enthusiasm for Christo-mimetic mortification of the flesh.